Application of the Wheat Processing Circle Quality Control Method In Raw Wheat Bin Silos To Reduce Defective Products - Susiati, Devi; ., Rivaldi (Tibuana, 2024)
The food industry is an industry that ranks first in Indonesia because it is basically a primary need. The food industry sub-sector, at 38.38%, breaking the USD 21.35 billion mark, supported the GDP of the non-oil and gas processing industry in the second quarter of 2022. The largest investment was in the food sector, including the bakery, flour, and palm oil industries. PT. XYZ is the largest company in Indonesia in the field of milling wheat into flour. This company experienced a problem in the screening area, namely rwb silos with a lot of husks in a month there were 20 incidents so it reached 80%. To overcome these problems, the QCC method approach is used. From the results of the analysis using the QCC method, it was found that the failure rate of raw wheat bin silos with lots of husks decreased from 20 in April to 0 in June by applying the standardization that had been obtained.